Multistakeholder's Roles in Creating Job Vacancy for Youth through Community Development - Azizah, Reni Nur; Wahyuni, Ekawati Sri; Mulyono, Pudji (International Journal Labs, 2023)
The development of the Wangsakerta youth community which has been carried out since 2016 has implications for the ability and innovation of the younger generation to take part in the non-formal sector which provides benefits for themselves and the surrounding community. Various self-development activities are carried out so that the younger generation is able to have self-confidence and be able to create various jobs independently. The purpose of this study was to analyze the influence of youth characteristics and youth participation on job creation according to social capital. This study uses a stakeholder analysis method using the penta helix. The results showed that academic stakeholders or IAIN Syekh Nurjati Cirebon played a role in organizing training activities to support the abilities and insights of the youth community at the Wangsakerta nature school. Business actor stakeholders play a role in establishing relationships such as non-governmental organizations through Ms. Farida Mahri, in this case the relationship creates partners for the development of Saung Wangsakerta to date. Communities or non-governmental organizations have a role in gaining relationships or networks for the development of the Saung Wangsakerta youth community. The government, through Karang Taruna, plays a role in helping in the development and construction of Saung Wangsakerta, such as participating in the construction of Saung or places of learning. The media plays a role as a publication in promotion. The village government is not involved as a controller, regulator and provider in the development of the Saung Wangsakerta youth community.